Aspectos macroscópicos e microscópicos da reparação de feridas cutâneas de camundongos (Swiss-valleé) tratadas com o creme de Hyptis suaveolens e Croton urucurana Baill - Antonio, Fátima Isabel (2005)
The use of medicinal plants has increased world wide. Therefore it is necessary to know their possible effects in order to establish their correct use. The objective of this study was to asses the effects of Hyptis suaveolens and Croton urucurana cream in the tissue repair of skin wounds. In the present experiment, it has been used 72 females, adults mice (Mus musculus) lineage suis (Swiss Vallé), with an approximately weight of 50 each. In each mice it was made a 10,0mm wound on its dorsal region. The mice were divided in three groups, named droups, I, II and III. The cutaneous wounds of group I were treated using base cream, group II with Hyptis suaveolens ointment and group III with Croton urucurana oitment.I In the third day of PO the wounds of group I, II and III have presented themselves dry, with regular borders. In the histological valuation were found significative differences between groups I and II, where group I presented a higher percentage of polimorphonuclear cells than group II, and the percentage of polimorphonucleares cell was higher than group III. In the seventh day of PO the group I wounds have presented with a humid aspect, irregular border, rose coloured and with an scab which could be detached easily. In the fourteenth day of PO it has been observed higher mononuclear cells in group I than in group II and higher polimorfphonuclear cells quantity than in group III. It has not been observed in neither groups a complete reepitelization in the fourteenth day of PO, however the wounds were more regular in groups II and III and possessed a more organized granulation tissue. In the twenty-first day PO the wounds areas of groups I, II and III did not differ statically, but it has been found a higher collagen percentage in group II than in group I and its granulation tissue was more organized than the other groups. We concluded the Hyptis suaveolens ointment performed a better reepitelization than the other groups.